Factors of ICT adoption and cultural preservation among the Kadazandusun community in Sabah - Fang, Yi Xue; Gill, Sarjit S.; Rosnon, Mohd Roslan; Talib, Ahmad Tarmizi (Human Resource Management Academic Research Society, 2021)
The development of Information and Communication Technology has also brought about changes to the cultural context of the community. This paper investigates the factors that influence the ICT adoption for cultural preservation among the Kadazandusun community in Sabah. This study adopted the Unified Theory of Acceptance and Use of Technology (UTAUT) which identifies four key factors, namely performance expectancy, effort expectancy, social influence, and facilitating conditions. In this study, a quantitative approach was used. This study included 350 Kadazandusun community members as respondents. To determine the mean of the four factors measured, a descriptive analysis was performed with a total mean score of 5.00. Performance expectancy had the highest mean score (4.06), followed by effort expectancy (4.03). The other two factors were slightly lower: social influence = 3.51 and facilitating conditions = 3.42. The findings revealed that ICT has indeed improved the Kadazandusun community's performance and effort in preserving their culture. The Kadazandusun community, on the other hand, can easily adopt ICT without much influence from the social circle. In terms of facilitating conditions, its score was the lowest indicating that the availability of tools, skills, financial resources, and facilities is critical to ensuring longterm ICT adoption.